Exploring COVID-19 pandemic perceptions and vaccine uptake among community members and primary healthcare workers in Nigeria: A mixed methods study - Abiodun Sogbesan; Ayobami Adebayo Bakare; Sibylle Herzig van Wees; Julius Salako; Damola Bakare; Omotayo E. Olojede; Kofoworola Akinsola; Oluwabunmi Roseline Bakare; Adegoke G. Falade; Carina King (PLoS ONE, 2026)
Background The COVID-19 pandemic significantly impacted global health, with diverse perceptions about the disease and its control measures, including vaccination. Understanding these perceptions can help inform public health and vaccination strategies in future outbreaks. This study examined community members and healthcare workers' (HCWs) perceptions of the COVID-19 pandemic and vaccines in Nigeria, exploring factors that influence vaccine acceptance and hesitancy. Methods We conducted a mixed-methods study, combining quantitative survey data from 2,602 respondents (2,206 community members and 396 HCWs) with qualitative interviews (14 HCWs and 16 community members). Quantitative data were analyzed to identify factors associated with COVID-19 vaccine uptake and pandemic perceptions, while qualitative insights provided a deeper understanding of cultural perceptions, experiences, and hesitancy towards the COVID-19 vaccine. Results Overall, 43.4% of community members and 96.7% of HCWs received at least one dose of the COVID-19 vaccine. Vaccine uptake was positively associated with increasing age, previous COVID-19 testing, male sex, government employment, and knowing someone diagnosed with COVID-19. Christianity was associated with lower uptake among community members. Perceptions varied, with 34.2% of community members and 17.7% of HCWs considering COVID-19 a death sentence, while 27.8% and 22.0% believed in ‘African immunity,’ respectively. Hesitancy was driven by the fear of side effects (32.6%), pregnancy-related concerns (25.9%), and convenience-related issues (13.5%). Qualitative data revealed misinformation, mistrust, fear of adverse reactions, logistical challenges, and belief in the sufficiency of childhood vaccination fueled hesitancy towards the COVID-19 vaccine. Despite this, general trust in vaccine safety and efficacy remained high, with most respondents willing to be vaccinated against other diseases and future outbreaks. Conclusion Our findings underscore the need for tailored public health strategies to address specific sociodemographic factors, individual perceptions, and logistical challenges to enhance COVID-19 vaccine uptake. Public health campaigns should focus on debunking myths, improving vaccine literacy, and leveraging the social influence of respected community leaders to build trust.